Eugenia velutifolia (Myrteae, Myrtaceae), a new species from the Cerrado of São Paulo, Brazil - Mazine, Fiorella Fernanda; Sant’ana, Gabriela Zominhani; Sobral, Marcos; Valdemarin, Karinne Sampaio (Phytotaxa, 2019)
Eugenia velutifolia is a new species of Myrtaceae from the Cerrado of São Paulo state, Brazil, which is here described, illustrated and compared morphologically with three similar species, E. bimarginata, E. livida and E. suberosa. It differs mainly from those species by the velutinous indumentum on both sides of the leaf blade and twigs, also by the larger sepals.